Advanced interatrial block predicts ineffective cardioversion of atrial fibrillation: a FinCV2 cohort study - Relander Arto; Hellman Tapio; Vasankari Tuija; Nuotio Ilpo; Airaksinen Juhani K. E.; Kiviniemi Tuomas (TAYLOR & FRANCIS LTD, 2022)
Aims: Rhythm control using electrical cardioversion (CV) is a common treatment strategy for patients with symptomatic atrial fibrillation (AF). To guide clinical decision making, we sought to assess if electrocardiographic interatrial blocks could predict CV failure or AF recurrence as the phenomenon is strongly associated with atrial arrhythmias.
Methods: This study included 715 patients who underwent a CV for persistent AF lasting >48 h. P-wave duration and morphology were analyzed in post-procedure or the most recent sinus rhythm electrocardiograms and compared with rates of CV failure and AF recurrence within 30 days after CV as well as their combination (ineffective CV).
Results: CV was unsuccessful in 63 out of 715 patients (8.8%) and AF recurred in 209 out of 652 (29.2%) patients within 30 days after CV. Overall, 272 (38.0%) CVs turned out ineffective. Advanced interatrial block (AIAB) defined as P-wave duration >= 120 ms and biphasic morphology in inferior leads (II, III and aVF) was diagnosed in 72 (10.1%) cases. AIAB was an independent predictor for CV failure (OR 4.51, 95%CI 1.76-11.56, p = .002), AF recurrence (OR 2.93, 95%CI 1.43-5.99, p = .003) and ineffective CV (OR 3.87, 95%CI 2.04-7.36, p < .001).
Conclusion: AIAB predicted CV failure, AF recurrence as well as their composite. This study presents an easy electrocardiographic tool for the identification of patients with persistent AF who might not benefit from an elective CV in the future. KEY MESSAGESInteratrial blocks are very common in patients with atrial fibrillation.Advanced interatrial block predicts ineffective cardioversion.